2000
DOI: 10.1073/pnas.97.7.3388
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 infection through the CCR5 receptor is blocked by receptor dimerization

Abstract: The identification of the chemokine receptors as receptors for HIV-1 has boosted interest in these molecules, raising expectations for the development of new strategies to prevent HIV-1 infection. The discovery that chemokines block HIV-1 replication has focused attention on identifying their mechanism of action. Previous studies concluded that this inhibitory effect may be mediated by steric hindrance or by receptor down-regulation. We have identified a CCR5 receptor-specific mAb that neither competes with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 42 publications
4
73
2
Order By: Relevance
“…The finding that complexes of defective CCR5 mutants mediate HIV-1 infection can appear to be contradictory with conclusions of a study linking the antiviral activity of an anti-CCR5 mAb (designated CCR5-02) to the dimerization of CCR5 that it apparently induced (36). Because the CCR5-02 mAb did not interfere with the surface expression and chemokine receptor activity of CCR5, the authors inferred that its conformation in the context of dimers does not permit a functional interaction with HIV-1.…”
Section: Functional Complementation Of Ccr5 Mutants 39394mentioning
confidence: 72%
See 2 more Smart Citations
“…The finding that complexes of defective CCR5 mutants mediate HIV-1 infection can appear to be contradictory with conclusions of a study linking the antiviral activity of an anti-CCR5 mAb (designated CCR5-02) to the dimerization of CCR5 that it apparently induced (36). Because the CCR5-02 mAb did not interfere with the surface expression and chemokine receptor activity of CCR5, the authors inferred that its conformation in the context of dimers does not permit a functional interaction with HIV-1.…”
Section: Functional Complementation Of Ccr5 Mutants 39394mentioning
confidence: 72%
“…This process was apparently constitutive and proposed to play a role in the routing of CCR5 to the cell surface. However, in other studies, dimers of the CCR2, CCR5, or CXCR4 were detected only if cells were treated with the cognate chemokine ligands (35)(36)(37) or with a monoclonal antibody in the case of CCR5 (36). In these different studies, dimers of …”
Section: Cooperation Of Wild-type Ccr5 and A Defective Mutant-thementioning
confidence: 99%
See 1 more Smart Citation
“…Among human CKRs, both CCR2 and CCR5 have been shown to form dimers upon ligand binding (43,49), and CCR5 dimerization has been presumed to modulate HIV entry (49) and T cell activation through the Jak signaling pathway (50). Ligandor antibody-induced CCR5 dimerization (49) and heterodimerization of CCR5 or CXCR4 with a natural CCR2 mutant allele, CCR2-V64I (51), have been proposed to hinder HIV infection. Using a yeast two-hybrid system, Benkirane et al (20) demonstrated that CCR5 formed dimers through sequence spanning the N terminus and the first TM domain.…”
Section: Discussionmentioning
confidence: 99%
“…Heterodimerization between related subunits of GPCRs may alter or expand ligand specificity (45), and some may function as oligomers in vivo (48). Among human CKRs, both CCR2 and CCR5 have been shown to form dimers upon ligand binding (43,49), and CCR5 dimerization has been presumed to modulate HIV entry (49) and T cell activation through the Jak signaling pathway (50). Ligandor antibody-induced CCR5 dimerization (49) and heterodimerization of CCR5 or CXCR4 with a natural CCR2 mutant allele, CCR2-V64I (51), have been proposed to hinder HIV infection.…”
Section: Discussionmentioning
confidence: 99%